Mitigating Shrinkage and Enhancing the Structure of Thermally Insulating Starch Aerogel via Solvent Exchange and Chitin Addition - Jacob Staker; Gracie M. White; Sevinch Pasilova; Daniel A. Scheiman; Haiquan Guo; Andres Tovar; Amanda P. Siegel (Macromol)
Bio-based compostable starch aerogels have significant potential as a sustainable alternative to traditional polymer aerogels across various applications. However, they suffer from very significant shrinkage, shown in published work as 40–50% using existing processes. We hypothesized that the shrinkage is largely caused by pore collapse through the solvent exchange process, during which the water used to fabricate the starch matrix is replaced with ethanol. To mitigate this issue, this work introduces two strategies: (1) implementing a deep-freezing protocol (DFP) prior to the solvent exchange, followed by pure ethanol solvent exchanges instead of water/ethanol mixtures, and (2) incorporating chitin as a structural additive. As a baseline, we fabricated potato starch aerogels (PSAs) using conventional processes of mixing, heating, and retrogradation. By applying a DFP before pure ethanol exchanges, shrinkage was reduced from 44% to 10% in pure PSA samples. Furthermore, the addition of chitin reduced shrinkage to 8% in potato starch-chitin aerogels. Porosity, density, surface area, pore size distribution, thermal decomposition temperature, thermal conductivities, and scanning electron microscopy images demonstrate a correlation between reduced shrinkage and desired thermal material properties.